Glial cells, but not neurons, exhibit a controllable response to a localized inflammatory microenvironment in vitro - Sommakia, Salah; Rickus, Jenna L.; Otto, Kevin J. (Frontiers in Neuroengineering, 2014)
The ability to design long-lasting intracortical implants hinges on understanding the factors leading to the loss of neuronal density and the formation of the glial scar. In this study, we modify a common in vitro mixed cortical culture model using lipopolysaccharide (LPS) to examine the responses of microglia, astrocytes, and neurons to microwire segments. We also use dip-coated polyethylene glycol (PEG), which we have previously shown can modulate impedance changes neural microelectrodes, to control the cellular responses. We find that microglia, as expected, exhibit an elevated response to LPS-coated microwire for distances of up to 150 µm, and that this elevated response can be mitigated by co-depositing PEG with LPS. Astrocytes exhibit a more complex, distance-dependent response, whereas neurons do not appear to be affected by the type or magnitude of glial response within this in vitro model. The discrepancy between our in vitro responses and typically observed in vivo responses suggest the importance of using a systems approach to understand the responses of the various brain cell types in a chronic in vivo setting, as well as the necessity of studying the roles of cell types not native to the brain. Our results further indicate that the loss of neuronal density observed in vivo is not a necessary consequence of elevated glial activation.